Natural greenhouse gas and ozone-depleting substance sources and sinks from the peat bogs of Connemara, Ireland from 1994–2020. Issue 6 (1st August 2021) - Derwent, Richard G.; Simmonds, Peter G.; O'Doherty, Simon J.; Spain, T. Gerard; Young, D.
Abstract : New emissions of methane and chloroform, with concurrent depositions of ozone and hydrogen were determined from the peat bogs of Ireland. Abstract : The peat bogs of Connemara in the vicinity of the Mace Head Atmospheric Research Station on the Atlantic Ocean coastline of Ireland act as natural sources and sinks of greenhouse gases and ozone-depleting substances. Simultaneous emissions of methane and chloroform occur routinely during night-time inversions and low wind speeds, with concurrent depositions of ozone and hydrogen. The temporally correlated ozone data were employed with the nocturnal box method to determine the deposition velocities of hydrogen and the emission rates of methane and chloroform during 502 night-time events over the study period from 1994–2020. The average hydrogen deposition velocity found was 0.45 ± 0.3 mm s −1 . Hydrogen deposition velocities appeared to increase with time by about +1.2% per year. Chloroform emission rates averaged 0.44 ng m −2 s −1 and were somewhat smaller than those we have reported previously. Methane emission rates averaged 0.37 ± 0.2 μg m −2 s −1 in agreement with our previous studies but this study found an increase with time of +1.3% per year which was statistically significant. This increase was probably driven by local climate change through the increasing rainfall seen during the study period.